A study on Clostridium spp. exposure level on infant population in some parts of China - Ying LI; Fengqin LI; Tao JIANG; Xiang LIU; Gaopeng LEI; Yuzhen CHEN; Lingling WU; Chengyu XUE; Xiaoning HU; Yinping DONG (Zhongguo shipin weisheng zazhi, 2020)
Objective A case-control study on Clostridium spp. contamination on infant population and infant formula powdered was carried out, the data on Clostridium spp. exposure in some parts of China was obtained. Methods Epidemiological information and samples were collected from 6 locations in 6 provinces in China. The isolation and identification, of Clostridium spp. were performed. Results Totally 501 infants were investigated. Among them, 247 were exclusive breastfeeding and 254 were mixed feeding. According to the month grouping, 367 were 0-6 months and 134 were 7-12 months. A total of 813 samples were collected. After testing, 246 strains of Clostridium spp. were obtained and the positive rate was 30.3% (246/813). C. sporogenes (8.4%, 68/813), C. bifermentans (6.2%, 50/813) and C. butyricum (4.6%, 37/813) had the highest detection rate.37.3% (187/501) of the stool samples were Clostridium spp. positive, followed by 22.3% (27/121) of the infant formula powder, 19.5% (25/128) of the environmental swab and 11.1% (7/63) of the food samples. The detection rate of Clostridium spp. in mixed feeding group was significantly higher than that of breast-feeding group (χ2=40.833, P<0.01), and 7-12-month-old group was significantly higher than that of 0-6 months group (χ2=27.829, P<0.01). Conclusion There was a high exposure level of Clostridium spp. in food and environment in infant population in some parts of China.